2000
DOI: 10.1143/jjap.39.l789
|View full text |Cite
|
Sign up to set email alerts
|

Control of the Conduction Type of Nondoped High Mobility β-FeSi2 Films Grown from Si/Fe Multilayers by Change of Si/Fe Ratios

Abstract: Highly [100]-oriented nondoped β-FeSi2 continuous films were grown on Si (001) substrates from Si/Fe multilayers with different Si/Fe ratios (1.6–2.0). It was found that the conduction type of the grown layer changed from p-type to n-type when the deposited Si/Fe ratio was increased, suggesting that the conduction type of nondoped β-FeSi2 is governed by stoichiometry. Annealing of the samples at 900°C for up to 14 h decreased the carrier density and increased the mobility, but did not change the conduction typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…In order to address these issues, several studies on iron silicides under pressure have been done [1][2][3]. On the other hand, iron and nickel silicides have received attention since their magnetic and electronic properties make them prospective materials for optoelectronics [4]. Finally, these silicides also produce oxides in which the Fe:Si (Ni:Si) stoichiometry is maintained.…”
Section: Introductionmentioning
confidence: 99%
“…In order to address these issues, several studies on iron silicides under pressure have been done [1][2][3]. On the other hand, iron and nickel silicides have received attention since their magnetic and electronic properties make them prospective materials for optoelectronics [4]. Finally, these silicides also produce oxides in which the Fe:Si (Ni:Si) stoichiometry is maintained.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22] Tani and Kido performed first-principles calculations of defects in b-FeSi 2 using density functional theory. They showed that Si vacancies have lower formation energies than Fe vacancies in b-FeSi 2 , and that crystals containing Si vacancies exhibit p-type conduction.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, FeSi 2 changes from semiconducting b-FeSi 2 to metallic a-Fe 2 Si 5 above 937 1C [8]. To date many types of film-growth methods have been developed, including molecular beam epitaxy (MBE) [9], chemical vapor deposition (CVD), RF-sputtering deposition and ion beam synthesis (IBS). An author of this paper has also reported b-FeSi 2 films before prepared by the IBS [10].…”
Section: Introductionmentioning
confidence: 99%